Accounting-Aware Evidence-Constrained Agents for Disclosure, Settlement, and Secondary-Market Risk Monitoring in Tokenized - Sihan Zhou; Yuanzheng Chen; Kenny Lee (Journal of Technology Informatics and Engineering, 2026)
Tokenized real-world asset (RWA) infrastructure exposes platform operators, investors, and reporting teams to a combined settlement, disclosure, liquidity, and accounting-quality monitoring problem. A tokenized claim can continue to trade while the underlying issuer releases new financial statements, securities fail to deliver in the reference market, or protocol-level liquidity changes in RWA venues. This paper develops an accounting-aware, evidence-constrained agent workflow for risk alerting and source-grounded report generation. The revised experiment replaces the earlier rule-generated monitoring sandbox with external datasets: SEC fails-to-deliver observations, SEC EDGAR XBRL company facts, SEC submissions metadata, Financial PhraseBank sentiment labels, and DefiLlama RWA protocol TVL. The issuer-day panel contains 2,648 surveillance tasks for eight large U.S. issuers from 2024-12-01 through 2026-03-31. Observed settlement stress is defined from external SEC FTD balances rather than from the agent's own rule. Accounting risk is computed from XBRL-derived liquidity, leverage, accrual, and cash-flow indicators. A stronger market-plus-accounting logistic baseline is added alongside single-source baselines and the proposed fusion agent. The machine-learning baseline achieves the strongest F1 score for settlement-stress detection (0.909), while the proposed fusion agent achieves the highest report faithfulness and tool-use correctness (1.000 each) and high recall (0.849). The results support a governance-oriented interpretation: an evidence-constrained agent is most useful not as an opaque high-accuracy classifier, but as an auditable layer that connects settlement evidence, filing metadata, accounting fundamentals, independent sentiment calibration, and RWA protocol liquidity into a reproducible monitoring record.